Dispensing of zolpidem and benzodiazepines in Brazilian private pharmacies: a retrospective cohort study from 2014 to 2021 - Carvalho, Fabiana; Tonon, André Comiran; Hidalgo, Maria Paz; Martins Costa, Manuela; Mengue, Sotero Serrate (Frontiers in Pharmacology, 2024)
Objective: The study aimed to evaluate Zolpidem and Benzodiazepines prescription and dispensing data in private pharmacies in Brazil from 2014 to 2021. Methods: This retrospective cohort study was carried out with retrospective open data from the Brazilian Federal Government from January 2014 to August 2021 containing medicines registered in the National Controlled Products Management System (SNGPC).Results: Between January 2014 and August 2021, a total of 32,441,392 sales of thirteen drugs from the z-drug and benzodiazepine classes used to treat sleep disorders were recorded in Brazil.Throughout the entire period, clonazepam emerged as the most popular drug, accounting for 29.8% of total sales. Alprazolam followed in second place with 20.6% of sales, while zolpidem came in third with 14.4%. The normal-release form of zolpidem was consistently the highestselling variant during the evaluation period. However, the fast-acting-release form exhibited the most significant growth, indicated by a noticeable upward trend in sales since 2020. In contrast, the extended-release form of zolpidem remained stable over the years.The increased sales of zolpidem in Brazilian private pharmacies raise concerns about potential misuse and dependence on this drug mainly for the treatment of insomnia.The epidemic of sleeping pills arises in a scenario of expectancy of short-term amelioration of symptoms, with no correspondence in best clinical practice. Education and counseling for both healthcare professionals and the general population are essential to address this growing health concern and ensure the safe and appropriate use of medications for sleep disorders.